Penerapan Metode FMEA (Failure Mode and Effect Analysis) Pada UD. Lajamin Untuk Memperbaiki Kualitas Produk Tas - Muhammad Zahidil Mukhtar; Moh. Jufriyanto; Yanuar Pandu Negoro (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2022)
UD. Lajamin is a trading business engaged in the bag production manufacturing industry. So far, the resulting bag products often experience defects that exceed the company's standards. To improve product quality, it is necessary to apply the FMEA method with the stage of identifying the type of defect, the cause of the problem and the consequence of the defect. Based on the FMEA method, defects with the highest RPN (Risk Priority Number) value that must be repaired such as untidy stitches, torn defects, accessories defects. This is used as the basis for making proposals to partners in community service activities to improve product quality and reduce product defects. Proposed improvements are socialized to partner business owners so that they can be well understood and accepted.